KAJIAN KELEMBAGAAN DAN PENGENDALIAN HAMA TERPADU PADA USAHATANI KAKAO DI KABUPATEN POLEWALI MANDAR SULAWESI BARAT - Muh. Taufik Taufik; Muhammad Sjafaruddin (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
Institutional and Integrated Pest Management Assessment of Cacao Farming System in Polewali Mandar District, West Sulawesi. Up to the present, experts of cacao are still looking for the solution to increase cacao products and cacao farmers' income, among them are the efforts of reinforcing cacao institutes and conducting suggested farming system. For example, the application Integrated Pest Management (IPM), especially to overcome the pest of cacao fruit (PBK), mouse and rotten disease of fruit. The components of IPM consist of (a) covering cacao fruit; (b) increasing harvest frequency; (c) sanitation; (d) fertilization; (e) clipping and (f) developing black ant. The study was executed at countryside in Kurma Village, District of Mapilli, Sub-Province of Polewali Mandar, West-Sulawesi in 2007. The areas used for this study covering a 20 hectares of land involving 25 cacao farmers that were attacked by cacao pest (PBK), mouse, and fruit rotten disease. The study includes three important aspects such as: (1) the institutes of cacao production farming, (2) the evaluation and verification of IPM at production scale, and (3) farmers' responSes. The research study indicated that institute of cacao production farming District of Mapilli, Sub-Province of Polewali Mandar was running towards the expected goal, because the production and maintenance of record data has been done. The production facilities and marketing of the institute needs guidance, because the price differences received by the farmers are still high ranging from 19% to 22%. The application of the IPM components package on farmers' land in technical and economical terms should be done considering that the income level of IPM farmers is higher compared to non-IPM farmers (i.e. Rp.13.376.180 and Rp.9.115.000 respectively). Key words: Institute, integrated pest management, cacao farming system Sampai saat ini, para pakar kakao masih mencari solusi untuk meningkatkan produksi dan pendapatan petani kakao. Upaya penguatan kelembagaan pada usahatani kakao dan menerapkan sistem budidaya yang dianjurkan. Penerapan paket Pengendalian Hama Terpadu (PHT), terutama untuk mengatasi hama Pengerek Buah Kakao (PBK), tikus dan penyakit busuk buah. Komponen PHT yang diterapkan adalah (a) penyarungan buah kakao; (b) panen sering; (c) sanitasi; (d) pemupukan; (e) pemangkasan dan (f) pengembangan semut hitam. Pengkajian dilaksanakan di Desa Kurma, Kecamatan Mapilli, Kabupaten Polewali Mandar, Sulawesi Barat, tahun 2007. Areal yang digunakan adalah pertanaman kakao yang terserang Hama PBK, tikus, dan penyakit busuk buah, dilakukan pada lahan petani dengan luas 20 ha, melibatkan 25 petani. Pengkajian mencakup tiga aspek utama yaitu: (1) Kelembagaan usahatani kakao, (2) Evaluasi dan verifikasi rakitan paket PHT pada skala produksi, dan (3) respon petani. Hasil pengkajian menunjukkan bahwa kelembagaan produksi usahatani kakao di Kecamatan Mapilli, Kabupaten Polewali Mandar sudah berjalan sesuai harapan, karena sudah melakukan kegiatan produksi dan pencatatan data hasil produksi. Kelembagaan sarana produksi dan pemasaran masih pembinaan, karena perbedaan harga yang diterima petani masih berkisar 19-22%. Penerapan komponen Paket PHT kakao di Lahan petani layak untuk dilaksanakan, baik secara teknis maupun secara ekonomis, dengan tingkat pendapatn petani pelaksana paket PHT mencapai Rp.13.376.180 jauh lebih besar dibandingkan dengan petani non PHT yaitu Rp.9.115.000. Kata kunci: Kelembagaan, pengendalian hama terpadu, usahatani kakao